Metallothionein–Kidney Bean Polyphenol Complexes Showed Antidiabetic Activity in Type 2 Diabetic Rats by Improving Insulin Resistance and Regulating Gut Microbiota - Zhaohang Zuo; Weiqiao Pang; Wei Sun; Baoxin Lu; Liang Zou; Dongjie Zhang; Ying Wang (Foods, 2023)
Previous studies have shown that interaction between polyphenols and proteins can benefit health, but the mechanism of its antidiabetic effect has not been thoroughly elucidated. Therefore, this study aimed to investigate the impact of the metallothionein (MT)–kidney bean polyphenol complex on the blood glucose levels and gut microbiota of rats with type 2 diabetes mellitus (T2DM) induced by a high-fat diet combined with streptozotocin (STZ). After 7 weeks of intervention, the MT–kidney bean polyphenol complex can significantly improve the loss of body weight, the increase in blood glucose and blood lipids, and insulin resistance caused by T2DM in rats. In addition, it can effectively alleviate the damage to the pancreas and liver in rats. The MT–kidney bean polyphenol complex also significantly increased the concentrations of six short-chain fatty acids (SCFAs) in the intestinal contents of rats, especially acetic acid, propionic acid, and butyric acid (296.03%, 223.86%, and 148.97%, respectively). More importantly, the MT–kidney bean polyphenol complex can significantly reverse intestinal microflora dysbiosis in rats caused by T2DM, increase intestinal microorganism diversity, improve the abundance of various beneficial bacteria, and reshape the gut microbiota. In summary, the hypoglycemic effect of the MT–kidney bean polyphenol complex and its possible mechanism was expounded in terms of blood glucose level, blood lipid level, and gut microbiota, providing a new perspective on the development of the MT–kidney bean polyphenol complex as functional hypoglycemic food.